Liposomal encapsulation of pro-NO donor drug - Koh, Cheryl Jie Yan (Nanyang Technological University, 2020)
Coronary artery disease was reported to be the third leading cause of mortality in Singapore in 2018. Due to the prevailing problem of atherosclerosis as a result of unhealthy eating habits, inactivity and age, remedies such as percutaneous intervention through the use of stents are in place. The focus of this project is to improve on current drug-eluting stents in the market, through using a pro-nitric oxide donor drug (S-nitrosoglutathione, GSNO), which is selective in nature, and provides a myriad of benefits to the body, potentially mitigating the problem of late stent thrombosis, as well as patients’ reliance on dual anti platelet therapy. The aim is to sustain the release of nitric oxide secreted from the drug, through the slow diffusion across the lipid bilayer of liposomes. Liposomes are utilised as drug carrier due to its biocompatibility and inert nature in the physiological body, to protect the drug as well as prevent premature elimination by the body. Herein, different phospholipids will be used to fabricate both neutral charged liposomes and negatively-charged liposomes, and their size stability characterized using Dynamic Light Scattering. The encapsulation of GSNO is first tested out using passive loading, followed by active loading, where results indicated that the loading efficiency by both methods are comparable. In-vitro release study conducted using Phosphate buffered saline solution found that the drug was not fully encapsulated in the core of the liposomes, resulting in complete release of nitric oxide within a day. Nonetheless, our findings suggest that Dipalmitoylphosphatidylcholine (DSPC) was the most stable and was able to mimic the desired sustained release profile, although more work still needs to be done to further finetune the experimental procedures to yield a better result.